GCC Monetary Union and the Degree of Macroeconomic Policy Coordination - Kamar, Bassem (IMF Working Papers; Working Paper ;, 2007)
Coordinating macroeconomic policies is a pre-requisite to a successful launch of the common currency in the GCC countries. Relying on the Behavioral Equilibrium Exchange Rate approach as a theoretical framework, we apply the Pooled Mean Group methodology to determine the similarity of the impact of a selected set of macroeconomic indicators on the real exchange rate in each country. Our empirical evidence points to a clear coordination of monetary policy, fiscal policy, government consumption, and openness across the member countries. While RER misalignments also show a substantial convergence building over time, differences in the misalignments of the two polar cases remain rather substantial, calling for further coordination and policy harmonization.